Himalayan black bulbuls (Hypsipetes leucocephalus niggerimus) exhibit sexual dichromatism under ultraviolet light that is invisible to the human eye - Hung, Hsin-Yi; Yeung, Carol K. L.; Omland, Kevin; Yao, Cheng-Te; Yao, Chiou-Ju; Li, Shou-Hsien (Springer Nature Limited, 2017)
Sexual dichromatism is a key proxy for the intensity of sexual selection. Studies of dichromatism in birds may, however, have underestimated the intensity and complexity of sexual selection because they used museum specimens alone without taking colour-fading into account or only measured conspicuous visual traits in live animals. We investigated whether the Himalayan black bulbul (Hypsipetes leucocephalus nigerrimus), which is sexually monomorphic to the human eye, exhibits sexual dichromatism distinguishable by a spectrometer. We measured the reflectance (within both the human visual perceptive and the ultraviolet ranges) of two carotenoid-based parts and eight dull and melanin-based parts for each individual live bird or museum skin sampled. According to an avian model of colour discrimination thresholds, we found that males exhibited perceptibly redder beaks, brighter tarsi and darker plumage than did females. This suggests the existence of multiple cryptic sexually dichromatic traits within this species. Moreover, we also observed detectable colour fading in the museum skin specimens compared with the live birds, indicating that sexual dichromatism could be underestimated if analysed using skin specimens alone.
Keywords: Himalayan black bulbuls; sexual dichromatism; ultraviolet light; invisible; human eye